PREPARE PRIMARY SCHOOL STUDENTS TO FACE THE TECHNOLOGICAL AGE: MATHEMATICAL CREATIVITY AND SPATIAL ABILITY - Rohman, Minanur (STAI Ma'had Aly Al-Hikam Malang, 2019)
Technology and mathematics are two things that are interconnected and influence. Technology, such as computer games, can be used to describe abstract mathematical concepts so that they are more easily understood by students. Unfortunately, technology also has some undesirable impacts, such as causing students difficulties in developing their creativity to understand mathematical concepts. On the other hand, spatial ability gets less attention than educators when students are studying mathematics. This paper will discuss how teachers can help students develop their mathematical creativity and spatial ability.